Effects of social support and self-efficacy on eHealth literacy in Korean women undergoing breast cancer treatment: A secondary analysis - Bang-Eun Lee; Ju-Yeon Uhm; Myoung Soo Kim (Elsevier, 2023)
Objective: Patients with breast cancer need to seek out and understand relevant health information to make informed decisions about long-term and complicated illnesses. With the increased use of interventions using online health information, research on eHealth literacy should be expanded. However, existing studies on the factors affecting eHealth literacy in patients with breast cancer are currently lacking. This study, therefore, conducts a secondary analysis of a previous study that surveyed the quality of life of patients with breast cancer. The primary study found a significant correlation between eHealth literacy, social support, and self-efficacy. In this secondary analysis study, we specifically examine eHealth literacy among patients with breast cancer undergoing treatment, and how patient demographic characteristics, breast cancer-specific self-efficacy, and social support contribute to their eHealth literacy. Methods: A total of 143 women receiving outpatient treatment or were hospitalized for breast cancer at a cancer hospital in South Korea participated in the study from January to November 2022. The eHealth Literacy Scale (eHEALS), Multidimensional Social Support Scale, and Breast Cancer Survivors Scale were utilized in the analysis. The data were analyzed using a multiple regression analysis. Results: Full-time employment (β ​= ​0.19, P ​= ​0.006), a monthly family income of over 4 million won (3600 USD) (β ​= ​0.14, P ​= ​0.042), completing a high school education (β ​= ​0.52, P ​< ​0.001), completing college level or higher education (β ​= ​0.54, P ​< ​0.001), age (β ​= ​−0.23, P ​= ​0.003), and social support (β ​= ​0.21, P ​= ​0.002) were predictors of eHealth literacy, explaining 40.2% of the total variance (F ​= ​14.63, P ​< ​0.001). Conclusions: Social support was identified as a new factor influencing eHealth literacy among patients with breast cancer undergoing treatment. Therefore, nursing interventions to strengthen social support should be developed to improve eHealth literacy.